Mengkaji Relasi Agama dan Ideologi - Hartanto, Roni Dwi (DINIKA : Academic Journal of Islamic Studies, 2016)
Abstract:Religion and ideology are two interesting terms to be discussed and researched. Both of the terms were able to give an ideal purpose of life which is desirable by every human being. Both of religion and ideology were able to give comprehensive description about the âideal-thingsâ which is intended by the human being to look for the happiness of life. Both of religion and ideology have properly arranged the way to achieve the âideal-conditionâ even needed serious struggle to realize it. Moreover, both of religion and ideology have also given inner satisfaction and strength to their followers. Religion and ideology can be illustrated as âboth side of coinâ which is interrelated. Ideology can be as religion because of its power which is able to make available of the âideal wayâ (solution) for its followers. As well as ideology, religion is not just spiritual way, but also able to make available âideal descriptionâ and straighten up the dimension of life, socially, politically, and also culturally.Â Keywords: Religion, Ideology, Relation of Ideology and Religion, Modernity, and genocide.